2012
DOI: 10.1128/jcm.06656-11
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) DNA Triage of Women with Atypical Squamous Cells of Undetermined Significance with cobas 4800 HPV and Hybrid Capture 2 Tests for Detection of High-Grade Lesions of the Uterine Cervix

Abstract: T he primary screening of cancer of the uterine cervix is based in most countries on Pap cytology testing. Women with an abnormal cytology are referred for colposcopy-directed biopsy to assess the presence and grade of cervical disease. In North America, for each new case of cervical cancer, there are between 50 and 100 cases of abnormal smears consistent with low-grade (LSIL) or high-grade squamous intraepithelial lesions (HSIL) (11). Additionally, there are at least twice as many cases of "atypical squamous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
3
20
1
Order By: Relevance
“…In recently published studies, Cobas HPV also showed comparable performances to HC2, with kappa coefficients from 0.69 to 0.87, but there also were discrepant results between HC2 and Cobas HPV in approximately 6% to 15% of the samples (10,20,34). In another recent study, Cobas HPV showed a clinical sensitivity of 89.7% and a specificity of 66.7% for detecting cases with CIN2 or worse-grade CINs, whereas HC2 demonstrated a better clinical sensitivity of 93.1% and a specificity of 72.2% (18). Differences in concordance rates between the HPV detection assays among the studies might result from differences in the analytical sensitivities for different HPV genotypes and differences in HPV genotypes among the constituent of subjects with HPV infections.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In recently published studies, Cobas HPV also showed comparable performances to HC2, with kappa coefficients from 0.69 to 0.87, but there also were discrepant results between HC2 and Cobas HPV in approximately 6% to 15% of the samples (10,20,34). In another recent study, Cobas HPV showed a clinical sensitivity of 89.7% and a specificity of 66.7% for detecting cases with CIN2 or worse-grade CINs, whereas HC2 demonstrated a better clinical sensitivity of 93.1% and a specificity of 72.2% (18). Differences in concordance rates between the HPV detection assays among the studies might result from differences in the analytical sensitivities for different HPV genotypes and differences in HPV genotypes among the constituent of subjects with HPV infections.…”
Section: Discussionmentioning
confidence: 96%
“…The two real-time PCR assays are suggested by their respective manufacturers to be able to detect 14 HR HPV genotypes (HPV types 16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 66, and 68). The results of the two assays are reported as either positive or negative for HPV types 16 and 18 and a pooled result for the remaining 12 HR genotypes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the specificity of cobas was comparable to that of HC2 in women referred with ASCUS. Most previous studies have evaluated the cobas for triage of ASCUS smears (3,4,5); few, if any, have included LSIL. Interestingly, in women referred with LSIL, the cobas test was more specific than HC2 for detection of CIN2ϩ (55.2% compared to 35.1%; McNemar P ϭ 0.001).…”
mentioning
confidence: 99%